Transformation of Military Robotics in Defense Systems: A Multi-Domain Capability Analysis - Nur Rachman Supadmana Muda; M. Faisal Fadilah; Ena Marlina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Robotic technology has become a critical component in modern military operations due to its ability to enhance operational effectiveness, improve battlefield awareness, and reduce risks to human personnel. The rapid advancement of artificial intelligence, autonomous systems, sensor technologies, and communication networks has significantly expanded the capabilities of military robots across land, air, surface, and underwater domains. This study examines the role of robotic technology in supporting combat operations, focusing on its applications in intelligence, surveillance, reconnaissance (ISR), force protection, logistics support, target acquisition, urban warfare, and electronic warfare. Military robotic systems, including Unmanned Ground Vehicles (UGVs), Unmanned Aerial Vehicles (UAVs), Unmanned Surface Vehicles (USVs), and Unmanned Underwater Vehicles (UUVs), provide enhanced operational flexibility and enable missions in hazardous environments where human deployment would be highly risky. Furthermore, the integration of artificial intelligence enables autonomous navigation, target recognition, sensor fusion, and real-time decision support, thereby improving mission efficiency and accuracy. The study also discusses key advantages of military robotics, including casualty reduction, increased mission endurance, and force multiplication capabilities. However, several challenges remain, such as cybersecurity vulnerabilities, communication disruptions, limited autonomy, energy constraints, and ethical concerns regarding autonomous weapon systems. Future developments are expected to focus on swarm robotics, human-robot teaming, AI-driven autonomy, multi-domain operations, and advanced energy systems. The findings indicate that robotic technology will continue to play an increasingly significant role in shaping future warfare by enhancing military capabilities while minimizing operational risks and human casualties.